DOI: 10.20868/upm.thesis.36489
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic forces on heave plates for offshore systems oscillating close to the seabed or the free surface

Abstract: xiv de la distancia al fondo marino o a la superficie libre.3. El comportamiento físico del flujo, para valores de KC cercanos a su valor crítico ha sido estudiado mediante el análisis del campo de vorticidad.4. Introducir porosidad al disco, reduce la masa añadida para los valores de KC estudiados, pero se ha encontrado que la porosidad incrementa el valor del coeficiente de amortiguamiento cuando se incrementa la amplitud del movimiento, logrando un máximo de damping para un disco con 10% de porosidad.5. Los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Recently, Garrido-Mendoza (2015) confirmed that there is a relatively weak dependence of the measured added masses with frequency and a large dependence with KC for one leg (cylinder + heave plate) of the semisubmersible used in this thesis. He also performed experimental scale effect with 3 different scales of such geometry on heave oscillation test, finding no relevance scale effect for such cases confirming the possible use of smaller scale on future experimental campaign.…”
Section: Damping Of Heave Motion In "Semi" Fowtssupporting
confidence: 71%
See 1 more Smart Citation
“…Recently, Garrido-Mendoza (2015) confirmed that there is a relatively weak dependence of the measured added masses with frequency and a large dependence with KC for one leg (cylinder + heave plate) of the semisubmersible used in this thesis. He also performed experimental scale effect with 3 different scales of such geometry on heave oscillation test, finding no relevance scale effect for such cases confirming the possible use of smaller scale on future experimental campaign.…”
Section: Damping Of Heave Motion In "Semi" Fowtssupporting
confidence: 71%
“…More recently, Garrido-Mendoza (2015) has validated Finite Volume Method (Open-Goam) to calculate axisymmetric viscous flow problem of heave plates oscillating in heave, the geometry used for validation is one leg of the one used in this thesis. He also performed a parametric study of such heave plates with different flaps using numerical tools, as well as determines the influence of bottom and free surface on damping and added The hydrodynamic load is strongly dependent on the hydrodynamic coefficients of the structure being deployed, but as it was mentioned before, the works developed up to now are focused on the geometrical features and motion features.…”
Section: Modelingmentioning
confidence: 99%
“…This may increase the system downtime or damage the components and acts as an important challenge which needs to be addressed. For this purpose, a possible solution is the inclusion of a heave plate [1], adopted in the SATH technology [2], which adds motion dampening mainly by viscous effects and other benefits for pitch and roll motions. This is not a common practice for oil rigs or the naval industry and, consequently, the engineering software typically employed needs to be revisited.…”
mentioning
confidence: 99%